Urban Chinese consumers willingness to use eco-friendly cutleries provided by catering takeaway - Zhu, Zhu; Isa, Siti Suriawati (Academia Industry Networks, 2022)
China, in recent years, has witnessed a large number of takeaway consumers and the staggeringly increasing use of takeaway Cutleries. In 2020, the Chinese government issued the "Opinions on Further Strengthening the Control of Plastic Pollution" forcing Chinese food and beverage takeaways to provide consumers with eco-friendly cutlery that meets the regulations. This study aims to understand the intention of Chinese takeaway consumers to use environmentally friendly cutlery so that the government and society can target and guide a large number of consumers to accept this change more rationally. Based on the TPB model, incorporating the findings of existing literature and adding the variable of consumers paying for environmentally friendly cutlery. Data were collected using a questionnaire to construct a scale of Chinese consumers' usage intention of eco-friendly cutlery provided by takeaway businesses/enterprises, and a final model test was obtained.